Dynamic stability of a blue multi-resonance thermally activated delayed fluorescence molecule without damaging the luminescence properties. Issue 14 (24th March 2023) - Zhang, Heming; Ke, Lianbao; Nie, Yufang; Wang, Jiaxuan; Bi, Hai
Abstract : Steric effect induced stability recovery between the triplet and singlet states. Abstract : The instability of blue emitters is one of the shortcomings of organic light-emitting diodes (OLEDs) in industrial applications. This instability is intrinsically associated with the basic transitions and reactions in the excited states. In this work, using the framework of Fermi's golden rule and DFT/TDDFT, the mechanisms of the transitions and reactions of a typical boron based multi-resonance thermally activated delayed fluorescence emitter involving the excited states were investigated. A dynamic stability mechanism describing recycling between the dissociation of the molecular structure in the T1 state and restoration in the S0 state dominated by steric effects was discovered. Applying knowledge of this mechanism, a small modification was made to the molecular structure, and the stability was increased without degrading other luminescence properties such as the luminescence color, FWHM, reverse intersystem crossing, fluorescence quantum yield, and internal quantum yield.